Economic evaluation of a general practitioner with special interests led dermatology service in primary care. Issue 7530 (8th December 2005) - Coast, Joanna; Noble, Sian; Noble, Alison; Horrocks, Sue; Asim, Oya; Peters, Tim J; Salisbury, Chris
Abstract: Objective To carry out an economic evaluation of a general practitioner with special interest service for non-urgent skin problems compared with hospital outpatient care. Design Cost effectiveness analysis and cost consequences analysis alongside a randomised controlled trial. Setting General practitioner with special interest dermatology service covering 29 general practices in Bristol. Participants Adults referred to a hospital dermatology clinic who were potentially suitable for management by a general practitioner with special interest. Interventions Participants were randomised 2:1 to receive either care by general practitioner with special interest service or usual hospital outpatient care. Main outcome measures Costs to NHS, patients, and companions, and costs of lost production. Cost effectiveness, using the two primary outcomes of dermatology life quality index scores and improved patient perceived access, was assessed by incremental cost effectiveness ratios and cost effectiveness acceptability curves. Cost consequences are presented in relation to all costs and both primary and secondary outcomes from the trial. Results Costs to the NHS for patients attending the general practitioner with special interest service were £208 (361; euro 308) compared with £118 for hospital outpatient care. Based on analysis with imputation of missing data, costs to patients and companions were £48 and £51, respectively; costs of lost production were £27 and £34, respectively. The incremental cost effectiveness ratios for general practitioner with special interest care over outpatient care were £540 per one point gain in the dermatology life quality index and £66 per 10 point change in the access scale. Conclusions The general practitioner with special interest service for dermatology is more costly than hospital outpatient care, but this additional cost needs to be weighed against improved access and broadly similar health outcomes.